FACTORS DETERMINING THE COMPARATIVE DIFFERENTIATION AND USE OF SYNONYMS IN ENGLISH AND UZBEK LANGUAGES (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Synonyms are an essential part of any language, providing speakers with multiple ways to express similar meanings with slight differences in nuance, style, or usage. In the context of English and Uzbek, two linguistically distinct languages, the differentiation and use of synonyms are influenced by several linguistic, cultural, historical, and social factors. A comparative analysis between the two languages reveals these influences on how synonyms evolve and are applied in different contexts.